Revised Upper Albian-Maastrichtian planktonic foraminiferal biostratigraphy and magnetostratigraphy of the classical Tethyan Gubbio section (Italy). - Coccioni, Rodolfo; Silva, Isabella Premoli (Newsletters on Stratigraphy, 2015)
The Tethyan pelagic sections at Bottaccione and Contessa Highway (Gubbio, Italy) are internationally recognized to be the standard reference sections for the Late Cretaceous to Eocene geomagnetic polarity time scale calibrated to the integrated planktonic foraminiferal and calcareous nannofossil biostratigraphy. Due to the presence of a gap within Chron C31n (upper Maastrichtian) in the Bottaccione section, we use two distinct portions of these sections to construct a complete and well-preserved composite stratigraphic record, here named 'Gubbio section', 333.1 m in thickness and similar to 36 myr in duration, that begins in the upper part of the Marne a Fucoidi and extends through the Scaglia Bianca and Scaglia Rossa to the Cretaceous/Paleogene boundary. A refined magnetostratigraphy and planktonic foraminiferal and calcareous nannofossil biostratigraphy is here presented for this stratigraphic succession. In particular, the recovery of planktonic foraminifera successfully disaggregated from the hard lithologies allows a more precise placement of bioevents including: 1) the lowest occurrence (LO) of Thalmanninella globotruncanoides defining the Albian/Cenomanian boundary, 2) the LO of Globotruncana linneiana approximating the base of the Santonian, 3) the LO of Pseudoguembelina palpebra approximating the base of the Maastrichtian, 4) the LO of Globotruncana aegyptiaca occurring earlier (upper Campanian) than previously recognized in the Gubbio area, and 5) the well-constrained pattern of the evolutionary history from Pseudotextularia elegans through Pseudotextularia intermedia and Racemiguembelina powelli to Racemiguembelina fructicosa. Moreover, the LO of Pseudoguembelina hariaensis, the highest occurrence (HO) of Gansserina gansseri and the LO of Plummerita hantkeninoides allow subdivision of the latest Maastrichtian into the Pseudoguembelina hariaensis, Pseudotextularia elegans and Plummerita hantkeninoides Zones. This refined magnetobiostratigraphic framework may improve reliability of Late Cretaceous ...